2016
DOI: 10.1038/ismej.2015.224
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and processes in microbial biogeography: do molecules and morphologies give the same answers?

Abstract: Our knowledge on microbial biogeography depends on the way we define and study diversity. In contrast to most microbes, some protist lineages have conspicuous structures that allow comparisons of diversity concepts and measures-those based on molecules and those based on morphology. We analyzed a group of shell-bearing planktonic ciliates, the tintinnids, in a coast-to-ocean gradient using highthroughput sequencing and microscopy. First, we compared molecular operational taxonomic units (OTUs) and morphospecie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 54 publications
(70 reference statements)
7
59
0
1
Order By: Relevance
“…We hypothesized that ciliate communities will be the similar in samples taken close together and that beyond some minimum distance, the community membership changes. We also expected to find strong assemblage changes related to the distance from shore as previously observed [16, 17, 19] such that communities are more diverse offshore. To evaluate these hypotheses, we contrasted the biogeographies of individual taxa (operational taxonomic units, or OTUs) with those of whole assemblages and evaluated patterns associated with physical and biological features of the environment.…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…We hypothesized that ciliate communities will be the similar in samples taken close together and that beyond some minimum distance, the community membership changes. We also expected to find strong assemblage changes related to the distance from shore as previously observed [16, 17, 19] such that communities are more diverse offshore. To evaluate these hypotheses, we contrasted the biogeographies of individual taxa (operational taxonomic units, or OTUs) with those of whole assemblages and evaluated patterns associated with physical and biological features of the environment.…”
Section: Introductionsupporting
confidence: 51%
“…Analyses of oligotrich and choreotrich ciliates, the main focus of the current study, have found complex patterns of diversity on a large spatial scale (transect of 130 km with samples every 6 km) [16, 17]. These studies reveal that the patterns of variation in ciliate communities are related to distance from shore and to the degree of water column stratification, as evidenced both by analyses of DGGE and HTS [16, 17, 19]. …”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…DNA sequencing has contributed to the study of protist communities, providing new insight into diversity (Pawlowski et al, 2016), predator-prey interactions (Martinez-Garcia et al, 2012), and discrepancies between morphologically defined species and genotypes (Stoupin et al, 2012;Santoferrara et al, 2016) .…”
Section: Introductionmentioning
confidence: 99%